Poaceae-specific cell wall-derived oligosaccharides activate plant immunity via OsCERK1 during Magnaporthe oryzae infection in rice - Chao Yang (Nature Portfolio, 2021)
Pathogen entry to plant cells can release cell wall components. Here the authors show that two endoglucanases secreted by the rice blast fungus Magnaporthe oryzae, produce specific oligosaccharides from rice cell walls that trigger immunity by promoting dimerization of OsCERK1 and OsCEBiP receptors.